Resistência à corrosão e cavitação de revestimentos FeMnCrSi depositados por processos de aspersão térmica de alta velocidade - Silveira, Luciana Leite (2018)
The cavitation and corrosion wear process on hydrodynamic components and systems dramatically reduces operational efficiency, leading to great economic losses. The use of wear resistant coatings has been studied as a solution to the problem of corrosion and cavitation in the industrial environment. The thermal spray processes are recognized as excellent approach to implementing high strength coatings as they allow the deposition of coatings with lower substrate change. The high velocity oxy-fuel (HVOF) process produces coatings with high density and cohesion. The high velocity air-fuel process (HVAF) is currently an alternative process to the HVOF, presenting equivalent and often superior properties to this process and at a lower operational cost. This research presents the use of HVOF and HVAF processes for the deposition of FeMnCrSi coatings, with the intent of studying the effects of the thermal spraying process and the chemical composition on the morphology, microstructure and resistance to cavitation and corrosion of the coatings. The work was divided in two parts, the first studied coatings of the same composition deposited by HVAF and HVOF as its morphology and resistance to cavitation and corrosion. The second part studied the influence of the chemical composition of four experimental alloys on the morphology and resistance to cavitation and corrosion of the coatings. The metallographic preparation of the coatings, analysis of morphology and defects in optical microscope and scanning electron microscope, Vickers microhardness test, accelerated cavitation and electrochemical corrosion tests were performed. The coatings deposited by the HVOF process presented higher amount of oxidation, related to the use of oxygen as oxidizer in this process. The HVAF process presented less oxidation of its coatings, by the use of compressed air as oxidizer instead of oxygen, besides higher values of fracture toughness, due to the higher particle velocities. This provided greater resistance to cavitation of the HVAF coatings. The corrosion resistance of HVAF coatings was also higher than HVOF coatings, due to a lower presence of oxides in the coatings, as they facilitate the penetration of ions into the coating, leading to internal corrosion. The chemical composition of the coatings deposited by HVAF had less influence on their oxidation and fracture toughness. The addition of boron was not beneficial to cavitation resistance. The corrosion resistance of coatings was positively influenced by the presence of Nickel. As for localized corrosion, a higher Chromium content was determinant in the higher resistance of the coatings.